Semiotic multimodality :a filmic analysis of Wong Kar-Wai's in the mood for love / - Tan, Chee Seng (University of Saint Joseph, 2017)
The study builts on Bateman and Schmidt’s (2011) and Tseng’s (2009) research on film as a form of “cinematographic document,” and continues their efforts to construct a semiotic mode of film. The author recognizes the complexity of undertaking research in the domain of semiotic discourse. This study argues that as film analysis is about ways of seeing and synthesizing different cinematic styles, strategies; learnt cinematic conventions and reflective viewing is imperative. The interaction of robust multimodal resources, well-defined analytic units, based on dependable models, and conducted through a discursive process should align to produce fruitful filmic discourse. The study premised on the assumption that film is more than a “self-enclosed signification system” but a crucial “cultural practice” that “reflect and inflect culture.” Taken together, this view underscores the importance and interactivity of cinema, culture and society. To this end, the study contributes to filmic meaning making, the New Hong Kong Cinema, and finally, the present study invariably serves as a form of “social document” or “cultural artifacts” in its exploration of Hong Kong ever changing identity, culture and moods.
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Interaction design for a contemporary learning and teaching environment: promoting independent learning at the primary level - Chan, Ka Chi (University of Saint Joseph, 2022)
The world is perpetually changing, and the COVID-19 pandemic has taught us that the future is full of unforeseen challenges and potentialities. What are the implications of the advancement in technology on education? How are teachers coping with contemporary educational expectations? Is there a need to redesign the learning environment? What is the exact nature of the forces driving such a change? Is there anything we can learn from successful innovations around the globe? The goals of this dissertation include designing a learning/teaching app and redesigning classroom furniture for primary-level education. A design thinking methodology is used, working through the phases of empathizing, defining, ideating, prototyping and testing the two potential designs
Keywords: Design; Interaction analysis in education; Interactive multimedia

An Attempt to Examine Digital Native and Digital Immigrant Macau Graphic Designers' Perceptions of Adopting Generative Design - Lau, Ching Man; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
The manifestation of generating digital visuals through an algorithm is gaining worldwide attention in the graphic design industry. It is a new form of computing that visualizes data input by the designer or collected in the physical environment and turns them into artwork. The generative design of...
Publisher: IGI Global

Applied Interactive Mindfulness: a virtual reality grave mourning user experience in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos (The creative process: reflections on contemporary creativity, 2022)
It has been proven in numerous research that mindfulness can be helpful to reduce stress and chronic pain (Hall, 2014; Lindström, n.d.; Tong et al., 2015). While interactive mindfulness has been one of the focuses in the recent mobile applications market, usually tackling three essential human senses: audio, visual, and touch, each mobile application has quite some different approaches in terms of interactivity. Some focus on the touch and visual, and some on audio (environmental sounds or instructing meditation). Immersing oneself in virtual reality (VR) creates a constant stream of interactivity. Nonetheless, what are the conditions for an (in)tangible virtual reality to be more effective? Under the COVID-19 pandemic and lockdown since the end of 2019, Macao has been facing a social concern that we cannot travel easily to visit our decedents’ graves abroad, let alone the existing concerns of expensive burial services, lack of space, and alternative burial options. Also, taking into consideration that standard funeral service in Macao is often too brief, and getting briefer, thus lacking the opportunity to properly farewell the decedent, this research is proposing a virtual reality 3D model construction of the Chapel of St. Michael, located in St. Michael the Archangel Cemetery in Macao, to be streamed on a 360 virtual tour platform, Kuula. co. By immersing in this virtual reality, the participant is to have a single user experience for mindfulness with the decedent. To ensure valid and reliable results that address the research aims and objectives, a single-user experiment is going to be set up with multiple electronic devices, namely, the smartphone iPhone X with cardboard VR, the tablet iPad Pro, and the Oculus Quest 2. The methodology to collect the data will be using observation and simulation. The experiment will be started with an introduction to the project and conducted with no instruction, allowing users to explore and examine all features in this immersive experience. Along with a post-experience survey (interview + questionnaire), we seek its conditions and impacts on Macao residents in terms of interactive mindfulness and participants’ expectation of testing, for the first time in Macao, a virtual reality grave mourning experience.

Editorial: On Cinema - Ribas, Daniel; Crespo, Nuno; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2020)
In the past decades, the field of cinema has undergone several transformations. The digital turn increasingly called for new forms of production, distribution, and exhibition, which imply different ways of thinking, doing, and experimenting cinema. These new forms also reduced the gap between cinema to other so-called visual arts. If cinema and visual arts were already in the process of merging, the last years forced the naturalization of thinking in similar theoretical grounds. This special issue aims to be a forum for the discussion of new practices of researching cinema, and the changes in cinema’s forms of experience and production.
Number: 2
Keywords: Art and cinema; Cinema; Contemporary cinema; Digital turn; Visual Arts

In Memorial and Serenity: Introducing VR Grave Mourning in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics, 2022)
Macao inhabit a population of 683,100. The birth rate has been dropping while the death rate has risen compared to two years ago. Cemeteries are becoming crowded, and burial spots are demanding. In this case, video calls and social media can be the solution. How about our beloved ancestors? Can we video call them on their memorial days? This paper presents a VR experience of immersing oneself in the 3D VR of the Chapel of St. Michael of Macao to create a peaceful atmosphere for grave mourning. The chapel is also a personal space where we can be truly isolated in serenity. It is a retreat to pray, disconnect, and reconnect to the beloved deaths that may not be buried in an easily accessible location. The authors propose a possible future of mourning our loved ones through virtual reality and telepresence: an immersive experience connected with Macao's extraordinary and cultural unicity.

ARTECH2017: Proceedings of the 8th International Conference on Digital Arts - Caires, Carlos; Cardoso, Jorge Carlos; Lipovka, Aleksei; Bidarra, José; Pimentel, Lúcia (Association for Computing Machinery, 2017)

A review of the Colloquium «Narrative, Media and Cognition» — a cartography of the borders of narrative - Castro, Maria Guilhermina; Caires, Carlos Sena; Ribas, Daniel; Palinhos, Jorge (Journal of Science and Technology of the Arts, 2015)
We present an overview and discussion of the Colloquium «Narrative, Media and Cognition», which took place at Porto's Centre of Catholic University of Portugal in July of 2015, under the organization of the Research Centre for Science and Technology of the Arts (CITAR). Several scholars of different areas presented research about the uses and advances in narrative study and practice in a broad range of areas, giving some important insights about the latest developments in Narrative Studies, Ontology of Narrative and the uses of Narrative in Art, Cinema, Performance, Journalism, Marketing and Literature, among other fields. After briefly describing the main points of each presentation in the Colloquium we try to draw some conclusions and possibilities raised by the Colloquium and take a glimpse of future paths that the use of Narrative can end up taking.
1 citations (Crossref) [2022-09-21] Artwork Size: 89-94 Páginas Publisher: Journal of Science and Technology of the Arts

Editorial - Castro, Maria Guilhermina; Palinhos, Jorge; Ribas, Daniel; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2017)
Number: 2

Editorial Preface - Marcos, Aderito; Caires, Carlos; Estadieu, Gerald; Mendes, Daniel; Rodrigues, Nuno (International Journal of Creative Interfaces and Computer Graphics, 2023)

Book of Proceedings of ARTeFACTo 2022 Macao, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities - Estadieu, G; Martins de Abreu, F.; Caires, Carlos; Fernandes Marco, A. (IEEE, 2023)

Editorial Preface - Estadieu, G; Marcos, Aderito; Caires, Carlos; Mendes, Daniel; Rodrigues, Nuno (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)

Towards an Approach to the Interactive Filmic Narrative - Caires, Carlos Sena (Image in the post-millennium: mediation, process and critical tension, 2021)

Design Thinking Methodology and Text-To-Image Artificial Intelligence: A Case Study in the Context of Furniture Design Education - Caires, Carlos Sena; Estadieu, Gerald; Olga Ng Ka Man, Sandra (Perspectives on Design and Digital Communication IV: Research, Innovations and Best Practices, 2024)
The design thinking methodology is a problem-solving approach that involves empathising with end-users, (re)defining problems, brainstorming solutions creatively, and experimenting with prototypes and testing. It has been widely adopted in education to help students develop critical thinking, creativity, and problem-solving skills in design. On the other hand, text-to-image artificial intelligence is a method used to generate images from natural language descriptors (usually referred to as prompts). Design thinking methodology can teach students to think creatively and critically about real-world problems when applied in the classroom. In the context of design teaching at the University of Saint Joseph, Macao, students use the design thinking methodology to develop innovative proposals for furniture design solutions. Combining design thinking methodologies with text-to-image artificial intelligence can further enhance the learning experience by allowing students to generate visual representations of their ideas during the ideation phase. The authors developed a systematic approach to generate images for ideation on furniture design based on prompting text-to-image (PTI). The analysis related students’ results who applied the design thinking methodology without using AI tools and the results generated using a standard text-to-image programme. By combining both methods, teachers can help students develop critical thinking, creativity, and problem-solving skills, while also allowing them to generate visual representations in a different paradigm and, by so, being able to communicate their ideas with the most appropriate support for them.
Keywords: Artificial intelligence; Design thinking; Education quality; Furniture design education; Text-to-image prompt

Empirical Studies on the Conditions of Achieving Interactive Mindfulness Through Virtual Reality Single User Experience in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (Entertainment Computing – ICEC 2023, 2023)
Virtual reality, a computer-generated 3D environment, allows one to navigate and possibly interact, resulting in real-time simulation of one or more of the user’s five senses (Gutierrez et al., 2008; Vince, 2004). Virtual tours and places have swiftly become popular in education, professional training, arts, exhibitions, and medication and rehabilitation. The empirical studies derived from the PhD thesis research aim to identify the conditions for Macao’s single-user experience to achieve mindfulness in virtual reality through immersion and interactivity.
Keywords: Single user experience; immersion; interactivity; mindfulness; virtual reality